Zwitterion‐Driven Shape Program of Prodrug Nanoassemblies with High Stability, High Tumor Accumulation, and High Antitumor Activity (Adv. Healthcare Mater. 23/2021). Issue 23 (8th December 2021) - Li, Guanting; Sun, Bingjun; Zheng, Shunzhe; Xu, Lu; Tao, Wenhui; Zhao, Dongyang; Yu, Jiang; Fu, Shuwen; Zhang, Xuanbo; Zhang, Haotian; Zhai, Yinglei; Luo, Cong; et al.
Abstract : Zwitterion Materials In article number 2101407 by Zhonggui He, Jin Sun, and co‐workers, prodrug nanoassemblies modified by PEG or zwitterion materials are presented as spherical soldiers or rod‐shaped soldiers. Through the voyage in the ocean, which indicates blood circulation, they reach the castle, which indicates tumors, in different ships. Soldiers ashore enter the castle through different gates, which indicate different endocytosis mechanisms, to play the role. Overall, the zwitterion‐modified rod‐shaped little soldiers ride a giant ship to the tumor sites and enter tumor cells through caveolin‐mediated endocytosis, leading to a highly effective drug delivery.